The system and basic methods of the human resource management in the domestic enterprises’ activity - Krivoruchenko, Alina; Shyshkin, Viktor (Management and Entrepreneurship: Trends of Development, 2017)
Business activity is often connected with non-standard situations that always require some unusual approaches to solve them. That’s why one of the most important tasks for any enterprise is its providing with reliable and competent personnel. The most significant factors of the entrepreneurial success are the formation of the qualified personnel structure and the improvement of the Human Resource Management System. The practical business activity attests to that organizations achieve success only in case of the effective team forming. Thus, the issue of Human Resource Management is sufficiently relevant today, because the success of any organization always depends on the human resources, which are the main driving force of the enterprise. Purpose. The subject of the study are the system and basic methods of the Human Resource Management at the enterprise. The main purpose of the paper is to analyze and evaluate the existing methods of the Human Resource Management. Also the article aims to determine the essence of the Personnel Management System of the enterprise. Design/methodology/approach. The basic principles of this research are the causality and objectivity principles, systematic and comparative methods, institutional and structural-functional approach. Findings. In this article the basic methods of the Human Resource Management and their main features are determined. This information can be used in the practical activity of the enterprises. Today the main methods that are widely distributed can be classified into three categories: The quantitative methods. The quality methods. The subsidiary methods. All of these methods have various drawbacks related to the insufficient disclosure of the practical aspects of their implementation. Today the enterprises need to take into account the technical, organizational, economic and physiological factors of their activity. It is important to mention that the comprehensive use of the named methods of the Human Resource Management is more effective and provides the possibility of the accurate forecast. Research limitations/implications. The scientific significance of the article consists in the analysis of the up-to-date methods of the Human Resource Management and their evaluation. Originality/value. The suggested in this article comprehensive use of the named methods of the Human Resource Management, taking into account the peculiarities of each approach separately, will further the increase of the Ukrainian enterprises’ competitiveness and will multiply their financial results. The implementation of these methods will increase the productivity and efficiency of their activity as well